(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article establishes that the financial security of joint stock companies is a concept of interdisciplinary, and its essence is determined by a wide range of concepts through the prism of the study of financial security as an economic, social and philosophical phenomenon. The problem of choosing a methodology for investigating the financial security of joint stock companies is the focus of not only financial scientific thought, but also individual philosophical studies. In order to comprehensively take into account all existing concepts and taking into account the importance of the philosophical foundations of financial security, the aim of the article is to maximally approximate financial security to the underlying principles of philosophy, as well as to establish the relationship between such scientific disciplines. The author proved that the problem of choosing the most appropriate methodology of financial security research of joint stock companies is closely interconnected with certain philosophical determinants of the system of financial security of corporate structures. The main philosophical determinants inherent in the financial security of joint-stock companies are systematized: financial security as a category of superstructures, interaction of external and internal, determinism of a phenomenon, unity of theory and practice. It is noted that financial security as an add-on category is reflected through internal and external relations; the interaction of internal and external manifests itself through the interconnections between the structural elements; determinism in financial security is manifested through the existence of tight dependencies between factors and performance; the principle of unity of theory and practice ensures the objectivity of research.